Usability Evaluation and Alternative Design Recommendations for HSIS Mobile Application: A Case Study of PT HNI - Harry Budi Santoso; Rozanah (The Indonesian Journal of Computer Science, 2024)
Halal Network International (HNI) is considered as one of the sharia MLM-based companies in Indonesia. In order to fulfill the sales management needs, HNI developed HSIS application. The aims of this study are to conduct usability testing and to design alternative interface design recommendations for the HSIS Mobile application by using the User-centered Design (UCD) process. This study applied the System Usability Scale (SUS) Questionnaire, Open-ended Question (OEQ), and Task Scenario within Usability Testing (UT) as research instruments. There were 81 respondents involved in filling out the questionnaires. Furthermore, UT Phase 1 was conducted by involving 14 respondents. The results of these processes were categorized, and the design solutions were mapped based on Nielsen's Ten Usability Heuristic of Interface Design and Shneiderman's Eight Golden Rules of Interface Design. The alternative design solutions were tested again in UT Phase 2 and they showed a significant decrease in the number of usability issues. Thus, it proves that the alternatives design can provide positive improvement in the usability and user experience of the HSIS Mobile application.